PERBEDAAN JARAK TEMPAT TINGGAL DARI LOKASI INDUSTRI GENTENG TERHADAP PENURUNAN FUNGSI PARU PENDUDUK DI DESA KEDAWUNG KECAMATAN PEJAGOAN KABUPATEN KEBUMEN - Widhiyanti, Erna; Widowati, Evi; Fibriana, Arulita Ika (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
The process of tile combustion produced air pollution in the form of dust and smoke which could influence degradation of lung function of the people around industry. There were 143 tile industries in Kedawung Village and it located near the residences. The purpose of this study was to know the difference between distance of shelter from the location of tile industry towards degradation of lung function of people in Kedawung village Pejagoan district, Kebumen regency. This research was using analytic observational with cross sectional approach. Population in this study were the people in Kedawung village. Sample amounted to 94 persons. Data analysis was carried out by univariat and bivariat (Chi Square). The results of this study was there was a difference between distance of shelter from location of tile industry towards decline in lung function of the people in Kedawung village Pejagoan district Kebumen regency (p=0,001). Suggestion for tile entrepreneurs is expected to make a higher chimney and reforestation around the chimney burning, for the example planting yellow palm. For those people who expected, during the day must close the window or other ventilation, make ventilation with a filter/filter type of fiberglass with price about Rp.600.000,- per meter